Drought in Sisal Territory: Study on the Standardized Precipitation Index (SPI) considering Climate Change Projections for Valente/BA - Cerqueira, Tiago Batista; Souza, Sueline S. De; Lobo, Alexandre Boleira; Vanderlei Silva, Marcos Antônio; Carmo Loiola, Marcos Victor do; de Santana, Luiz Antônio Costa; Cerqueira Santos, Marcos Antônio; Cocozza, Fábio Del Monte; Araújo, Jairton Fraga (International Journal of Advanced Engineering Research and Science, 2022)
This article aims to analyze the historical behavior and projections of precipitation and drought incidence for the municipality of Valente in Bahia, also associating climate variability with the variability of sisal production in the region. The research was characterized as exploratory descriptive, having been carried out through bibliographical and documentary survey. It should be noted that meteorological data were obtained through the platforms of the National Institute of Meteorology - INMET and Climate Change Projections for South America regionalized by the ETA - PROJETA model, which were analyzed using the Drought Index and Monitoring System - DIMES, to obtain the Standardized Precipitation Index – SPI and by CLIMAP to understand the trends and temporal distribution of rainfall and temperature for the location. The study concluded that in the 2010s there was one of the most severe and prolonged droughts today, which even influenced the low productivity of sisal in the region, and that, in view of future projections until 2030, the socioeconomic drought scenario tends to worsen.